Business Insights Unveiled: A Journey through Linear Programming Problems - Jha, Aditya; Sahani, Suresh Kumar; Jha, Anshuman; Sahani, Kameshwar (Mikailalsys Journal of Mathematics and Statistics, 2023)
This project delves into the world of linear programming problems (LPP), a powerful optimization technique. It delves into the historical background, key features, fundamental assumptions, and wide-ranging applications of LPP. It also explores two hypothetical case studies: one in investment portfolio optimization and the other in advertisement budget allocation. LPP serves as a guiding light in making strategic investment decisions by maximizing returns and minimizing risks. In the context of advertising, it enables efficient budget allocation to reach the maximum audience and achieve the highest impact within constraints. The project emphasizes how LP simplifies complex decision-making processes, highlighting its practicality and relevance across diverse sectors. In essence, linear programming emerges as an indispensable tool for informed, data-driven decision-making, much like a skilled navigator guiding a ship through challenging waters toward its destination.